Between the baroque and the illustration: three Murcian libraries of the old regime - García Cuadrado, Amparo (Revista General de Información y Documentación, 2017)
The article carries out an analysis of the collections belonging to three libraries of the Old Regime, using post-mortem three inventories dated in 1697, 1733 and 1790 as a main source of information. These are linked bibliographical collections - grandfather, son and grandson - belonging to a family of the Murcian patriciate, the Fontes Carrillo de Albornoz and their descendants. This chronological sequence has allowed to observe the existence of the "inherited library", the "personal library" and even the "shared library" in the case of the last of the collections. Facing the Baroque character of the first two, we can find the illustrated collection of the director of the Royal Economic Society of Friends of the Country in Murcia, Antonio Fontes Ortega. The study of these three libraries makes possible to know the uses followed in the transmission of the bibliographic heritage among the nobility, the number of books owned, the intellectual preparation due to the education received, and the degree of penetration of the culture prevailing in these representatives of the ruling elite of the ancient Kingdom throughout a century.